2015
DOI: 10.1109/map.2015.2480078
|View full text |Cite
|
Sign up to set email alerts
|

Design of Indoor WLANs: Combination of a ray-tracing tool with the BPSO method

Abstract: This paper presents an approach that combines a ray tracing tool with a binary version of the particle swarm optimization method (BPSO) for the design of infrastructure mode indoor wireless local area networks (WLAN). The approach uses the power levels of a set of candidate access point (AP) locations obtained with the ray tracing tool at a mesh of potential receiver locations or test points to allow the BPSO optimizer to carry out the design of the WLAN. For this purpose, several restrictions are imposed thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
(60 reference statements)
0
11
0
1
Order By: Relevance
“…Moreno et al combined a ray tracing tool with BPSO to design indoor wireless local area network (WLAN) (Moreno et al. 2015 ). The power levels of candidate access points (APs) are acquired by the ray tracing tool at potential receiver locations, and are optimized by BPSO.…”
Section: Binary Metaheuristic Algorithms In Applicationsmentioning
confidence: 99%
“…Moreno et al combined a ray tracing tool with BPSO to design indoor wireless local area network (WLAN) (Moreno et al. 2015 ). The power levels of candidate access points (APs) are acquired by the ray tracing tool at potential receiver locations, and are optimized by BPSO.…”
Section: Binary Metaheuristic Algorithms In Applicationsmentioning
confidence: 99%
“…The channel assignment problem in a multiradio wireless mesh network has been the subject of many recent studies [ 3 , 13 , 21 , 33 38 , 47 ]. Many methods were used in those solutions such as graph-based [ 48 , 49 ], optimization-based [ 37 , 45 , 50 ], and artificial intelligence-based [ 37 , 39 , 40 , 51 ] techniques. A detailed review of those methods can be found in the following surveys [ 3 , 7 , 52 ].…”
Section: Related Workmentioning
confidence: 99%
“…Esses estudos não avaliam elementos chave, como a demanda de tráfego requerida, a densidade de usuários, o balanceamento de carga ou a atribuição de canais. Neste sentido, Moreno et al (2015) propuseram uma técnica para maximizar a cobertura da rede, enquanto a quantidade de APs instalados era minimizada, variando a cobertura dos APs. Esta técnicaé conceitualmente similar ao método cell breathing, comumente utilizado em redes de telefonia celular.…”
Section: Trabalhos Relacionadosunclassified